The fracture-controlled carbonate Brejões Karst System mapped with UAV, LiDAR, and electroresistivity in the Irecê Basin - Brazil. (November 2022) - Furtado, Carla P.Q.; Borges, Sergio V.F.; Bezerra, Francisco H.R.; de Castro, David L.; Maia, Rubson P.; Teixeira, Washington L.E.; Souza, Anderson M.; Auler, Augusto S.; Lima-Filho, Francisco P.
Abstract: Understanding how fractures influence fluid flow in carbonate rocks is essential to understanding karst evolution, oil reservoirs, and aquifer exploitation. The present study investigates karst fracture geometry at the surface and subsurface in the Irecê Basin, a Neoproterozoic epicontinental cratonic basin in the São Francisco Craton, Brazil. We used an Unmanned Aerial Vehicle (UAV) to map both fractures in three outcrops and valley geometries, Light Detection And Ranging (LiDAR) to map 3500 m of cave conduits, and Electrical Resistivity Tomography (ERT) to identify karst zones between 90 and 110 m deep. Our results indicate that the Brejões Karst System is comprised of dissolution and collapse features such as caves, dolines, pavements, and karst valley. The quantitative analysis of subseismic fractures (<50 m long) identified 4398 fractures in Outcrop A, 2458 in Outcrop B, 4374 in Outcrop C, and 7172 in 18 cross-sections of the Brejões Cave. These fractures form a corridor with four main sets striking N–S, NNE–SSW, NW–SE, and E–W, where the fracture system is essential to cave connectivity, permeability, and development. The highest frequency of fractures coincides with the main cave axes, where the intersection of the fracture/fault are sites prone to dissolution. The ERT profiles indicated a high density of geophysical anomalies that correspond to enlarged fractures in the epikarstic zone that extend between the surface and approximately 30 m deep. The cave infill impacts the cave characterization and leads to underestimating cave dimensions. This study may contribute to an underestimation of the role played by subseismic scale fractures in karst evolution in gently deformed settings. Graphical abstract: Image 1 Highlights: The karst comprises river valley, cave, dolines and enlarged fractures. Four sets of subseismic fractures (<50 m long) control the karst system. Karstification enhanced fluid flow within a fracture corridor. We used ground-based LiDAR in subseismic-scale reservoir analog. We integrated digital outcrop of cave with Electrical Resistivity Tomography.